Case report: PSMA PET/CT addresses the correct diagnosis in a patient with metastatic prostate cancer despite negative core biopsies and mpMRI. A diagnostic challenge - Vetrone, Luigia; Cuzzani, Giulia; Mei, Riccardo; Zanoni, Lucia; Bertaccini, Alessandro; Bianchi, Lorenzo; Castellucci, Paolo; Gaudiano, Caterina; Cappelli, Alberta; Giunchi, Francesca; Fanti, Stefano (Frontiers in Oncology, 2023)
This is a case of [68 Ga]Ga-Prostate-specific membrane antigen (PSMA)-11 PET/CT in a 73-years old patient presenting high Prostate Specific Antigen (PSA) levels despite both multi-parametric magnetic resonance imaging (mpMRI) and 12-core saturation biopsy negative for prostate cancer (Pca). This is a highly interesting case because, despite the advanced metastatic spread at initial presentation as showed by [68Ga]Ga-PSMA-PET/CT, the primary Pca was detected by none of the diagnostic techniques (12 random sample biopsy, mpMRI, PSMA PET/CT). However, [68Ga]Ga-PSMA-PET/CT showed a suspicious axillary lesion suitable for biopsy, which finally resulted as Pca metastasis. This case report is therefore a brilliant example of how [68Ga]Ga-PSMA-PET/CT optimized patient’s management.